Pisarze wczesnochrześcijańscy na temat antykoncepcji - Kamczyk, Wojciech (Vox Patrum, 2025)
This article addresses the issue of the presence and moral evaluation of contraception in early Christianity. It analyzes the writings of Christian authors from the 2nd to the 6th century, distinguishing them from testimonies concerning abortion and infanticide. Using the historical-philological method, the study examines how the Church Fathers constructed their arguments: from references to the natural purpose of sexual acts (Athenagoras, Clement of Alexandria, Lactantius), through the condemnation of contraceptive practices (Hippolytus, Augustine), to defining contraception as a form of murder or sacrilege (Jerome, John Chrysostom, Caesarius of Arles). The article also discusses the penalization of such acts in the synodal legislation of Western Christianity (Martin of Braga). The primary sources analyzed include patristic texts by Augustine, Jerome, John Chrysostom, and Caesarius of Arles. The main conclusion is that contraceptive practices were seen as fundamentally contrary to the order of creation and were regarded as serious moral transgressions. The article contributes to the study of marital ethics and the perception of corporeality in Christian antiquity.